PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR BIOLOGI SISWA - Tami Subekti; Suwarto Suwarto; Anwari Adi Nugroho (BIO-PEDAGOGI, 2019)
This study aims to improve student activity and learning outcomes by using the Problem Based Learning (PBL) model in the XI grade of Mathematics and Natural Sciences at Veterans 1 Sukoharjo in the 2018/2019 academic year. This type of research is Classroom Action Research (CAR) which consists of 3 cycles, each cycle including planning, implementing, observing, reflecting. Data collection techniques using 1) observations, 2) assessment tests, 3) student observation sheets and 4) documentation. The results showed that the learning activities of cycle I were 21%, cycle II 60%, and cycle III 86%. Learning outcomes show that the first cycle was 47% (11 students), second cycle was 65% (15 students), and third cycle was 83% (19 students). Based on the results of the study it can be concluded that the PBL model can increase learning activities and biology learning outcomes in class XI students of Veterans 1 Sukoharjo.